121k views
2 votes
16h - 9 = -13 - 6h - 18

h=

16h - 9 = -13 - 6h - 18 h=-example-1

2 Answers

3 votes

Answer:

-1

Explanation:

16h+6h=-18-13+9

22h=-31+9

h=-22/22

h=-1

User Quayshawn
by
5.9k points
1 vote

Answer:

h = -1

Explanation:

Solve for h:

16 h - 9 = -6 h - 31

Add 6 h to both sides:

16 h + 6 h - 9 = (6 h - 6 h) - 31

6 h - 6 h = 0:

16 h + 6 h - 9 = -31

16 h + 6 h = 22 h:

22 h - 9 = -31

Add 9 to both sides:

22 h + (9 - 9) = 9 - 31

9 - 9 = 0:

22 h = 9 - 31

9 - 31 = -22:

22 h = -22

Divide both sides of 22 h = -22 by 22:

(22 h)/22 = (-22)/22

22/22 = 1:

h = (-22)/22

The gcd of -22 and 22 is 22, so (-22)/22 = (22 (-1))/(22×1) = 22/22×-1 = -1:

Answer: h = -1

User Polaris
by
5.4k points